Maternal Deaths caused by COVID-19 Infection in the First Year of the Pandemic Wave - Muhammad Ilham Aldika Akbar; Pungky Mulawardhana; Manggala Pasca Wardhana; Khanisyah Erza Gumilar; Ecccita Raheestyningtyas; Muhammad Ardian Cahya Laksana; Jimmy Yanuar Anas; Ernawati; Hermanto Tri Joewono; Muhammad Adrianes Bachnas; Brahmana Askandar Tjokroprawiro (Folia Medica Indonesiana, 2023)
Highlights: